Identification and Comparative Analysis of Long Non-coding RNAs in High- and Low-Fecundity Goat Ovaries During Estrus - Li, Yaokun; Xu, Xiangping; Deng, Ming; Zou, Xian; Zhao, Zhifeng; Huang, Sixiu; Liu, Dewu; Liu, Guangbin (Frontiers in Genetics, 2021)
The ovary is the most important reproductive organ in goats and directly affects their fecundity. Long non-coding RNAs (lncRNAs) are involved in the biological processes of oocyte maturation and ovarian carcinogenesis. However, in the context of reproduction in goats, few studies have explored the regulation of lncRNAs. Therefore, we herein used the ovaries of high and low fecundity Leizhou black goats to identify differentially expressed lncRNAs (DElncRNAs) by high-throughput RNA sequencing; moreover, we analyzed the target genes of lncRNAs by functional annotation to explore the role of DElncRNAs in ovarian development. Twenty DElncRNAs were identified, of which six were significantly upregulated and 14 were significantly downregulated in high fecundity goats. Gene ontology analyses suggested that MSTRG.3782 positively influences the expression of the corresponding gene API5, exerting regulative effects on the development of ovarian cancer, through which litter size might show variations. Further, as per Kyoto Encyclopedia of Genes and Genomes pathway analyses, MSTRG.2938 was found to be significantly enriched, and we speculate that MSTRG.2938 regulates ribosomal biogenesis in the pre-snoRNP complex as well as cell transformation and tumor growth in eukaryotes. Quantitative real-time PCR results were consistent with sequencing data. To conclude, our findings suggest that some lncRNAs play a key role in regulating tumorigenesis and cell division during ovarian development in goats.